2018
DOI: 10.5812/ans.67845
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship Between Serum Sodium Concentration and Mortality Rate in ICU Patients with Traumatic Brain Injury

Abstract: Background: Traumatic brain injury (TBI) is a major cause of death and disability globally, and serum sodium disorders are the most common and probably the most poorly understood electrolyte disorders in neurological diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…20 Hypernatremia is a common finding seen in TBI patients, with some studies reporting a prevalence of 30-40% in some instances. 4,6,21 It has also been found that patients with hypernatremia tend to be associated with more severe form of TBI. 7 Our study showed that 50% of total hypernatremia cases had sustained severe TBI 11 (50) followed by moderate 7 (31.8) and mild 4 (18.2) forms of TBI, but didn't show the statistically significant association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Hypernatremia is a common finding seen in TBI patients, with some studies reporting a prevalence of 30-40% in some instances. 4,6,21 It has also been found that patients with hypernatremia tend to be associated with more severe form of TBI. 7 Our study showed that 50% of total hypernatremia cases had sustained severe TBI 11 (50) followed by moderate 7 (31.8) and mild 4 (18.2) forms of TBI, but didn't show the statistically significant association.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, if chronic hyponatremia is rapidly corrected, osmotic demyelination occurs, which is potentially fatal. 4 Although multiple excellent studies have been conducted on hyponatremia and hypernatremia in patients with TBI, not many studies have incorporated dysnatremia as a whole and its outcome on the basis of severity, mode of injury, and clinical progress in a single study. [4][5][6][7] In this study, we have assessed the association of hyponatremia and hypernatremia with the severity of traumatic brain injury and its impact on mortality among TBI patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that hyponatremia is a common finding in patients with TBIs,[ 15 16 ] which has not been the case in this study. Another study has shown that sodium concentration has no effect on the prognosis of these patients,[ 17 18 ] but studies have shown that administration of hypertonic saline in patients with changes in cranial pressure can reduce cerebral edema and improve the prognosis while keeping plasma sodium higher. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…This is a descriptive analytical study conducted in 2018 on 70 patients with head trauma under mechanical ventilation who were admitted to the intensive care unit for more than 24 hours. They were selected based on a convenience sampling technique and inclusion criteria which were: having endotracheal intubation, head injury, age 18 years and above, no underlying heart, lung, kidney and thyroid diseases, and Glasgow Coma Scale (GCS) ≥9 [25]. On the other hand, exclusion criteria were: surgery during the study, transfer to another section, spontaneous exit of the endotracheal tube, phosphorus level > 5 mg / dl (hyperphosphatemia) and magnesium level> 2.8 mg /dl (hypermagnesemia).…”
Section: Methodsmentioning
confidence: 99%